The Investigations on the Faunal Compositions in Stored Products: II. The Faunal Composition in Relation to Kinds of Stored Products - KIRITANI, Keiji (Japanese Journal of Applied Entomology and Zoology, 1957)
In the previous paper, the writer discussed the effects of climate, altitude and the degree of civilization on the faunal composition of stored products pests. The present investigations aim to make clear to what extent the faunal compostion of stored products pests is affected by the kinds of stored products. 1. The collections were made from 210 plots including farmers, residences of consumers, mills and rationing centers that are situated at 7 localities in Kinki district from August to November in 1953 and in May, 1955. A total of 319 samples including rice, wheat, barley, wheat flour and rice bran were collected from the 210 plots. 2. As in the previous paper, the index of finding frequency (I) and s.p. ratio were used. The I. is a value which shows roughly the level of the population of the species concerned, and it is calculated by the following: I=number of plots in which the species concerned is present/total number of plots examined×100The s.p. ratio (the ratio of the total finding frequency of secondary pests to that of the primary pests) represents a characteristic of faunal composition of stored products pests. For example, if the secondary pests are more abundant than the primary pests, the s.p. value becomes above 1.0 (Table 1). 3. The s.p. value of milled products (wheat flour and rice bran) shows nearly three times higher than that of grain in both Lepidoptera and Coleoptera. The rice weevil (Calandra oryzae) and the almond moth (Ephestia cautella) are abundant both on milled products and grain. The cadelle (Tenebroides mauritanicus) and the Indian meal moth (Plodia interpunctella) have the higher I. value on grain, on the contrary, the red flour beetle (Tribolium castaneum) has the higher I. value on milled products. 4. The s.p. values of both Lepidoptera and Coleoptera on rice is higher than those on wheat and barley. The higher s.p. value on rice is mainly due to the fact that most of the samples were polished rice. The faunal difference between polished and unpolished rice is shown in Tables 3 and 4 mainly based on the samples collected in July, in Kyoto City. The s.p. value of polished rice is more than twice as high as that of unpolished rice, and the number of species of secondary pests is larger on polished rice. The higher I. values of both the saw-toothed grain beetle (Oryzaephilus surinamensis) and the red flour beetle on rice than those on wheat and barley are due to the same reason as mentioned above. The rice weevil and the cadelle were the dominant species on rice as well as on wheat and barley. As for Lepidoptera, the Indian meal moth on rice, the Angoumois moth (Sitotroga cerealella) on wheat and barley show the higher frequency, respectively. 5. The red flour beetle and the almond moth were the characteistic species on rice bran. 6. A list of stored products insects which were found under these investigations is presented in Table 5 with the food habits of each species. 65 species were recorded, but 75 individual moths including their larvae could not be determined. All of the mites were included under the heading of Acarina. 7. The most common pests found on stored products in descending order of their findin frequencies were: the rice weevil, the cadelle, the corn sap beetle (Carpophilus dimidiatus), the varied carpet beetle (Anthrenus verbasci), the red flour beetle and the saw-toothed grain beetle of coleopterous species, and the almond moth, Aglossa dimidiata, the Indian meal moth, the Angoumois moth and Aphomia gularis of lepidopterous species. 8. A few of the lesser grain borer (Rhizopertha dominica) were obtained only once in a warehouse. Owing to the post-war food situation, long term torage that offers a condition to develop heavy infestation has become comparatively rare.